Preparation method and application of GO / ZIF-8 / CMC composite aerogel
Through the preparation method of GO/ZIF-8/CMC composite aerogel, the shortcomings in adsorption performance and structural stability of rGO aerogel are solved, and efficient adsorption and removal of heavy metal ions in wastewater are achieved, and excellent mechanical stability and recycling are achieved.
Patent Information
- Application Number
- CN202510045497.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
AI Technical Summary
The existing rGO aerogels have shortcomings in adsorption performance and structural stability, and it is difficult to effectively remove heavy metal ions in wastewater.
Using the preparation method of GO/ZIF-8/CMC composite aerogel, composite aerogel with excellent mechanical stability and adsorption ability is prepared by combining graphene oxide, ZIF-8 and carboxymethyl cellulose together, and ultrasonic dispersion and hydrothermal self-assembly reaction.
The composite aerogel has good adsorption effect in a wide acid-base range, significantly improves adsorption performance and structural stability, is suitable for large-scale production, and supports recycling and environmentally friendly characteristics.
Smart Images

Figure HDA0005238278520000011 
Figure HDA0005238278520000012 
Figure HDA0005238278520000013
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a GO / ZIF-8 / CMC composite aerogel in the technical field of novel functional polymer materials, belonging to the technical field of aerogels. Background Art
[0002] Water pollution is a major social problem that has negative impacts on human health, sustainable development and the environment. Water-soluble pollutants such as heavy metal ions pose a great threat to water resources and ecosystems. A variety of methods have been developed to remove heavy metal ions from wastewater, including chemical precipitation, photocatalysis, flotation, ion exchange, remediation, electrochemical treatment, adsorption, membrane technology and coagulation / flocculation, etc. Thousands of studies have shown that adsorption is a mature and powerful method for removing dyes and heavy metal pollutants from wastewater due to its simple operation, low cost, environmental protection and good adsorption. Among them, carbon-based materials have been shown to be particularly suitable for the adsorption of heavy metal ions due to their high surface area and ability to produce different functional groups, including 1D-carbon nanotubes, 2D-graphene, biochar, etc.
[0003] Graphene oxide (GO) is a derivative of graphene. Its surface contains abundant oxygen-containing functional groups, which makes it very hydrophilic. Graphene oxide can be easily modified to increase its adsorption capacity for pollutants and improve its ability to inactivate harmful microorganisms in water. Although graphene oxide (GO) and reduced graphene oxide (rGO) are the two most prominent graphene derivatives, rGO has properties that GO does not have, such as hydrophobicity, super mechanical strength, better network structure, water retention capacity and large specific surface area. However, the widespread application of these low-dimensional nanomaterials is limited by the difficulty of heavy stacking and solution recovery. After a series of explorations and studies, the assembly of low-dimensional nanomaterials into 3D macrostructures has been proven to be one of the most promising ways to solve the above challenges. The fact that rGO aerogel can be effectively used to remove heavy metals and organic compounds from wastewater has been confirmed by many studies. However, the adsorption performance and structural stability of pure rGO aerogel are poor, so it needs to be functionalized to enhance its adsorption performance and structural stability.
[0004] Carboxymethyl cellulose is a natural polymer material that comes from nature. It is inexpensive, widely available, biodegradable, has good oxygen permeability, and contains rich functional groups. It is a very environmentally friendly material. Summary of the invention
[0005] The invention provides a method for preparing aerogel by composite of carboxymethyl cellulose, ZIF-8 and graphene oxide. The obtained composite aerogel has excellent mechanical stability, adsorption capacity, good biodegradability and recyclability, can work in a wide acid-base range, and has good adsorption effect in sewage treatment. The invention has a simple process flow, a simple preparation method and is convenient for large-scale production.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing a GO / ZIF-8 / CMC composite aerogel, the specific steps are as follows:
[0008] (1) dispersing graphene oxide GO in water to obtain a graphene oxide dispersion;
[0009] (2) dissolving dimethyl imidazole zinc salt ZIF-8 in ammonia water, dissolving carboxymethyl cellulose CMC by heating with water, and adding them together to the graphene oxide dispersion prepared in step (1), and ultrasonically dispersing for 10 to 30 minutes to obtain a mixed solution;
[0010] (3) adding a reducing agent to the mixed solution of step (2) to carry out a hydrothermal self-assembly reaction to obtain a composite hydrogel, and freeze-drying to obtain a GO / ZIF-8 / CMC composite aerogel.
[0011] Step (2) Carboxymethyl cellulose is dissolved by heating water to above 40°C.
[0012] The zinc dimethyl imidazole salt (ZIF-8) in step (2) is a metal organic framework material with a zeolite framework structure. The ZIFS material has potential application value in many fields such as gas storage and separation, heterogeneity, chemical sensors, biomedical imaging and drug delivery. The present invention uses water and methanol as solvents and adopts a room temperature solution precipitation method to prepare the material. The specific preparation process is as follows:
[0013] Dissolve Zn(NO3)2·6H2O (zinc nitrate hexahydrate) in deionized water, stir magnetically for 1 to 2 hours to disperse it evenly to obtain a zinc nitrate solution, dissolve 2-methylimidazole in methanol, stir magnetically for 1 to 2 hours to disperse it evenly to obtain a 2-methylimidazole solution, then slowly pour the zinc nitrate solution into the 2-methylimidazole solution, stir magnetically for 12 to 16 hours to disperse it evenly, and it is found that the mixed solution gradually becomes turbid, and as the stirring time gradually increases, the solution becomes milky white, and then it is centrifuged, freeze-dried, and ground to obtain dimethylimidazole zinc salt ZIF-8 powder.
[0014] The mass ratio of the Zn(NO3)2·6H2O (zinc nitrate hexahydrate) to 2-methylimidazole is 4 to 8:1.
[0015] The mass ratio of graphene oxide GO, dimethyl imidazole zinc salt ZIF-8 and carboxymethyl cellulose CMC in the mixed solution of step (2) is 1-3:0.1-0.5:0.25-1.
[0016] In step (3), the reducing agent is thiourea CH4N2S, and the mass ratio of graphene oxide to thiourea CH4N2S is 1:3-4.
[0017] The temperature of the hydrothermal self-assembly reaction in step (3) is 90-100° C., and the reaction time is 5-7 hours.
[0018] The present invention also provides the GO / ZIF-8 / CMC composite aerogel prepared by the preparation method as an adsorbent to adsorb heavy metal ions in sewage.
[0019] The present invention has the following beneficial results:
[0020] The reduced graphene oxide prepared by the present invention does not use the traditional reducing agent, but uses thiourea, which is an organic small molecule containing sulfur and nitrogen. Its thiol (-SH) and amino (-NH2) can react with heavy metal ions (such as Cd 2+ , Pb 2+ ) to form a stable chelate to further enhance the adsorption capacity. Thiourea can not only reduce GO, but also introduce sulfur- and nitrogen-containing functional groups on the graphene surface, which can improve the adsorption and catalytic properties of the composite material.
[0021] The reduction effect of thiourea used in the present invention can usually be achieved at a relatively low temperature, thus avoiding the destruction of the microstructure of the material by a high temperature environment. It not only retains the abundant adsorption sites and large specific surface area of graphene oxide, but also increases its strength and has a strong hydrophobic property. Then, a metal organic framework is introduced, which has abundant functional groups and is extremely environmentally friendly, thus ensuring the excellent hydrophobic property of the aerogel, enhancing the Young's modulus of the graphene aerogel, and significantly improving the adsorption performance of the material.
[0022] The invention adds metal organic frameworks and organic high molecular polymers, which can not only effectively improve the adsorption performance, but also realize recycling and recycling without causing secondary pollution to the environment, effectively enhance the structural stability and adsorption capacity of graphene oxide, and when the composite aerogel is used in sewage treatment, pollutants such as metal ions in the sewage are adsorbed on the surface and pores of the composite aerogel, thereby achieving the purpose of purifying water quality.
[0023] The composite aerogel prepared by the invention has a complete appearance, a compact structure, a low density and a high specific surface area. In the process of treating organic wastewater, the composite aerogel exists in a block form, thereby avoiding loss and improving the stability of the reaction operation.
[0024] The preparation method of the present invention will not change the performance of other aspects of the graphene aerogel, and the synthesis process is mild, relatively simple, and low in cost, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The scanning electron microscope image and pore size analysis image of the prepared ZIF-8;
[0026] Figure 2 The formation diagram of GO / ZIF-8 / CMC composite aerogel prepared with different GO and ZIF-8 ratios (i.e. different GZ);
[0027] Figure 3 The photos and scanning electron microscope images of the prepared GO / ZIF-8 / CMC aerogel;
[0028] Figure 4 The adsorption data of rGO aerogel, GO / ZIF-8 composite aerogel, and GO / ZIF-8 / CMC composite aerogel at different pH values;
[0029] Figure 5 The adsorption of Cd on GO / ZIF-8 / CMC composite aerogel at different adsorption times 2+ The adsorption condition.
[0030] Figure 6 This is the cyclic adsorption situation of GO / ZIF-8 / CMC composite aerogel. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the examples, but the embodiments and protection scope of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art.
[0032] The zinc nitrate hexahydrate used in the examples was purchased from the market, analytically pure (AR), with a molecular weight of 297.49; the 2-methylimidazole was purchased from the market, analytically pure (AR), with a molecular weight of 82.106; and the density of methanol was 0.791-0.793 g / mL.
[0033] Example 1
[0034] Using water and methanol as solvents, dimethylimidazole zinc salt ZIF-8 was prepared by room temperature solution precipitation method. The specific preparation process is as follows:
[0035] Weigh 4 mg of Zn(NO3)2·6H2O (zinc nitrate hexahydrate) and dissolve it in 2 mL of deionized water, and stir it magnetically at room temperature for 1 hour to evenly disperse it to obtain a zinc nitrate solution; dissolve 1 mg of 2-methylimidazole in 8 mL of methanol, and stir it magnetically at room temperature for 1 hour to evenly disperse it to obtain a 2-methylimidazole solution. Then slowly pour the zinc nitrate solution into the 2-methylimidazole solution, and stir it magnetically at room temperature for 12 hours to evenly disperse it. It is found that the mixed solution gradually becomes turbid, and as the stirring time gradually increases, the solution becomes milky white. Then it is centrifuged, freeze-dried, and ground to obtain dimethylimidazole zinc salt ZIF-8 powder.
[0036] like Figure 1 The figure shows the ZIF-8 prepared in Example 1, a is the scanning electron micrograph of ZIF-8, and b is the pore size distribution of ZIF-8. It can be seen that it exhibits an obvious hexahedral structure, and its size is about 268 nm.
[0037] Example 2
[0038] Using water and methanol as solvents, dimethylimidazole zinc salt ZIF-8 was prepared by room temperature solution precipitation method. The specific preparation process is as follows:
[0039] Weigh 6 mg of Zn(NO3)2·6H2O (zinc nitrate hexahydrate) and dissolve it in 2 mL of deionized water, and stir it magnetically at room temperature for 1 hour to evenly disperse it to obtain a zinc nitrate solution; dissolve 1 mg of 2-methylimidazole in 8 mL of methanol, and stir it magnetically at room temperature for 1 hour to evenly disperse it to obtain a 2-methylimidazole solution. Then slowly pour the zinc nitrate solution into the 2-methylimidazole solution, and stir it magnetically at room temperature for 14 hours to evenly disperse it. It is found that the mixed solution gradually becomes turbid, and as the stirring time gradually increases, the solution becomes milky white. It is then centrifuged, freeze-dried, and ground to obtain dimethylimidazole zinc salt ZIF-8 powder.
[0040] Example 3
[0041] Using water and methanol as solvents, dimethylimidazole zinc salt ZIF-8 was prepared by room temperature solution precipitation method. The specific preparation process is as follows:
[0042] Weigh 8 mg of Zn(NO3)2·6H2O (zinc nitrate hexahydrate) and dissolve it in 4 mL of deionized water, and stir it magnetically at room temperature for 1 hour to evenly disperse it to obtain a zinc nitrate solution; dissolve 1 mg of 2-methylimidazole in 16 mL of methanol, and stir it magnetically at room temperature for 1 hour to evenly disperse it to obtain a 2-methylimidazole solution. Then slowly pour the zinc nitrate solution into the 2-methylimidazole solution, and stir it magnetically at room temperature for 16 hours to evenly disperse it. It is found that the mixed solution gradually becomes turbid, and as the stirring time gradually increases, the solution becomes milky white. It is then centrifuged, freeze-dried, and ground to obtain dimethylimidazole zinc salt ZIF-8 powder.
[0043] Example 4
[0044] A method for preparing a GO / ZIF-8 / CMC composite aerogel, the specific steps are as follows:
[0045] S1. Prepare 10 mL of GO dispersion with a concentration of 6 mg / mL and stir overnight at room temperature to make it evenly dispersed;
[0046] S2. Take the ZIF-8 prepared in Example 1, dissolve the ZIF-8 in 3 mL of 25% ammonia water at a ratio of GO:ZIF-8=1:0.25, and stir magnetically to disperse it evenly to obtain a ZIF-8 solution;
[0047] S3, weigh 15 mg of CMC and dissolve it in 10 mL of ultrapure water at a temperature of 40° C. After stirring evenly, mix the GO dispersions, ZIF-8 solution, and CMC dispersions prepared in steps S1, S2, and S3 together, and stir magnetically for 30 min to obtain a mixed solution;
[0048] S4. According to the mass ratio of GO to CH4N2S of 1:3, CH4N2S was added to the mixed solution, ultrasonically dispersed for 30 minutes, and then placed in an oven at 95°C for hydrothermal reduction for 5 hours to obtain a composite hydrogel. The composite hydrogel was transferred to a refrigerator at -50°C and frozen for 12 hours. The frozen composite hydrogel was then transferred to a freeze drying oven and freeze-dried at -50°C for 48 hours to obtain GO / ZIF-8 / CMC composite aerogel.
[0049] According to the method of Example 4, the mass ratio of graphene oxide and ZIF-8 GO:ZIF-8 was adjusted to 1:0 (i.e., step S2 was not performed and ZIF-8 was not added), 1:0.1, 1:0.25, 1:0.5, 1:0.8, and 1:1, and the other steps were the same as in Example 4 to prepare different aerogels.
[0050] like Figure 2As shown in the figure, the prepared GO / ZIF-8 / CMC composite aerogels are different photos. It can be seen from the figure that when the ratio of GO:ZIF-8 aerogel is 1:0.8 and 1:1, the graphene aerogel cannot be formed, indicating that too much ZIF-8 will cause the self-assembly of graphene oxide sheets, resulting in the failure of the formation of graphene oxide aerogel.
[0051] like Figure 3 It is the GO / ZIF-8 / CMC composite aerogel prepared in Example 4. The aerogel is light in weight. It can be seen from Figure (a) that it presents a regular cylindrical structure and a relatively smooth surface. The prepared aerogel is relatively successful. Figure (b) is a scanning electron microscope image of the aerogel. It can be seen from the figure that it has fewer pores and is mainly in the form of flakes, indicating that the addition of ZIF-8 and CMC reduces the pores of the aerogel. However, the addition of the composite material introduces a large number of oxygen-containing functional groups, provides a large number of adsorption sites, and greatly increases its adsorption performance.
[0052] Example 5
[0053] A method for preparing a GO / ZIF-8 / CMC composite aerogel, the specific steps are as follows:
[0054] S1. Prepare 10 mL of GO dispersion with a concentration of 6 mg / mL and stir overnight at room temperature to make it evenly dispersed;
[0055] S2. Take the ZIF-8 prepared in Example 1, dissolve the ZIF-8 in 3 mL of 25% ammonia water at a ratio of GO:ZIF-8=1:0.25, and stir magnetically to disperse it evenly to obtain a ZIF-8 solution;
[0056] S3, weigh 30 mg of CMC and dissolve it in 10 mL of ultrapure water at a temperature of 45° C. After stirring evenly, mix the GO dispersions, ZIF-8 solution, and CMC dispersions prepared in steps S1, S2, and S3 together, and stir magnetically for 30 min to obtain a mixed solution;
[0057] S4. According to the mass ratio of GO to CH4N2S of 1:4, CH4N2S was added to the mixed solution, ultrasonically dispersed for 30 minutes, and then placed in an oven at 90°C for hydrothermal reduction for 7 hours to obtain a composite hydrogel. The composite hydrogel was transferred to a refrigerator at -50°C and frozen for 12 hours. The frozen composite hydrogel was then transferred to a freeze drying oven and freeze-dried at -50°C for 48 hours to obtain GO / ZIF-8 / CMC composite aerogel.
[0058] Example 6
[0059] A method for preparing a GO / ZIF-8 / CMC composite aerogel, the specific steps are as follows:
[0060] S1. Prepare 10 mL of GO dispersion with a concentration of 6 mg / mL and stir overnight at room temperature to make it evenly dispersed;
[0061] S2. Take the ZIF-8 prepared in Example 1, dissolve the ZIF-8 in 4 mL of 25% ammonia water at a ratio of GO:ZIF-8=1:0.25, and stir magnetically to disperse it evenly to obtain a ZIF-8 solution;
[0062] S3, weigh 60 mg of CMC and dissolve it in 10 mL of ultrapure water at a temperature of 50° C. After stirring evenly, mix the GO dispersions, ZIF-8 solution, and CMC dispersions prepared in steps S1, S2, and S3 together, and stir magnetically for 30 min to obtain a mixed solution;
[0063] S4. According to the mass ratio of GO to CH4N2S of 1:3.5, CH4N2S was added to the mixed solution, ultrasonically dispersed for 30 minutes, and then placed in an oven at 100°C for hydrothermal reduction for 5.5 hours to obtain a composite hydrogel. The composite hydrogel was transferred to a refrigerator at -50°C and frozen for 12 hours. The frozen composite hydrogel was then transferred to a freeze drying oven and freeze-dried at -50°C for 48 hours to obtain GO / ZIF-8 / CMC composite aerogel.
[0064] Comparative Example 1
[0065] The preparation method of rGO (reduced graphene oxide) aerogel, the specific steps are as follows:
[0066] S1. Prepare 10 mL of GO dispersion with a concentration of 6 mg / mL, add 3 mL of 25% ammonia water, and stir evenly;
[0067] S2. Add 180 mg of thiourea CH4N2S to the above GO solution (according to the mass ratio of GO: reducing agent = 1:3);
[0068] S3. The above solution was ultrasonically dispersed for 30 minutes, then placed in an oven and reacted at 95°C for 5 hours to obtain a hydrogel, the hydrogel was transferred to a refrigerator at -50°C and frozen for 12 hours, the frozen hydrogel was transferred to a freeze drying oven, and freeze-dried at -50°C for 48 hours to obtain rGO aerogel.
[0069] Comparative Example 2
[0070] A method for preparing a GO / ZIF-8 composite aerogel, the specific steps are as follows:
[0071] S1. Prepare 10 mL of GO dispersion with a concentration of 6 mg / mL and stir overnight at room temperature to make it evenly dispersed;
[0072] S2. Take the ZIF-8 prepared in Example 1, dissolve the ZIF-8 in 3 mL of 25% ammonia water at a ratio of GO:ZIF-8=1:0.25, and stir magnetically to disperse it evenly to obtain a ZIF-8 solution;
[0073] S3: The GO dispersion and ZIF-8 solution of steps 1 and 2 are mixed together, and magnetic stirring is performed for 30 minutes. Then, CH4N2S is added to the mixed solution according to the mass ratio of GO:CH4N2S=1:3, and ultrasonic dispersion is performed for 30 minutes. Then, the mixture is placed in an oven at 95°C for hydrothermal reduction for 5 hours to obtain the prepared composite hydrogel. The obtained hydrogel is transferred to a refrigerator at -50°C and frozen for 12 hours. The frozen hydrogel is transferred to a freeze drying oven and freeze-dried at -50°C for 48 hours to obtain a GO / ZIF-8 composite aerogel.
[0074] Example 7
[0075] The adsorption performance of heavy metal ions was studied, with Cd ions as the representative heavy metal ion. The specific steps are as follows:
[0076] 50 mL of a Cd ion solution with a concentration of 500 mg / L was prepared, and its pH value was adjusted to 1, 2, 3, 4, 5, and 6 with 0.1 mol / L NaOH solution and hydrochloric acid, respectively. Subsequently, 20 mg of the GO / ZIF-8 / CMC composite aerogel prepared in Example 4, the rGO aerogel prepared in Comparative Example 1, and the GO / ZIF-8 composite aerogel prepared in Comparative Example 2 were added to the Cd ion solution at each pH value, and their concentrations were measured by ICP to calculate their adsorption amounts.
[0077] The results are as follows Figure 4 As shown in Figure 2, with the increase of pH, the three aerogels have different 2+ The adsorption of all materials showed an increasing trend, but the adsorption effect can be clearly seen: GO / ZIF-8 / CMC composite aerogel>GO / ZIF-8 composite aerogel>rGO aerogel, indicating that the addition of metal organic framework ZIF-8 and polymer material CMC increased its adsorption sites and significantly improved its adsorption performance for heavy metal ions.
[0078] The adsorption experiment of GO / ZIF-8 / CMC composite aerogel was carried out under the condition of pH=6. The results are shown in Figure 5As shown in the figure, the overall adsorption amount in the adsorption experiment increases with the increase of time. The adsorption rate is the fastest and the increase of adsorption amount is the largest in the first two hours of the adsorption experiment. As time goes by, the adsorption rate gradually slows down, the increase of adsorption amount decreases, and it tends to adsorption equilibrium. In the first two hours of adsorption, the adsorption of heavy metal ions is faster. This is because at the beginning, the aerogel has a large number of adsorption sites. As the adsorption time increases, a large number of adsorption sites are occupied, so the adsorption efficiency slows down. After 10 hours of adsorption, the adsorption reaches equilibrium.
[0079] Cyclic adsorption regeneration experiment of GO / ZIF-8 / CMC composite aerogel:
[0080] The aerogel prepared in Example 4 was placed in 500 mg / L Cd 2+ The heavy metal ions were adsorbed by slowly stirring at room temperature in the solution. After 10 hours, several milliliters of the heavy metal ion solution were taken and centrifuged. The supernatant was then taken and its concentration was detected by ICP. After adsorption, the aerogel was soaked in 0.1 mol / L hydrochloric acid for desorption. After desorption for 10 hours, it was washed with ultrapure water and then freeze-dried at -50°C for 48 hours. The results were obtained in the next use. Figure 6 As shown in the figure, in the first adsorption experiment, the adsorption of heavy metal ions can reach 263 mg / g. With the increase of the number of cycles, the adsorption amount is 256 mg / g, 242 mg / g, 237 mg / g, and 228 mg / g. It can be seen that with the increase of the number of repeated uses, the adsorption of heavy metal ions Cd by GO / ZIF-8 / CMC composite aerogel is better. 2+ The adsorption amount of GO / ZIF-8 / CMC composite aerogel decreased, but its adsorption amount remained high, indicating that GO / ZIF-8 / CMC composite aerogel is a suitable aerogel for removing Cd from water. 2+ It is a good adsorption material and can be recycled.
[0081] Through the above embodiments and test results, it can be seen that the GO / ZIF-8 / CMC composite aerogel prepared by the present invention has a large specific surface area and a porous structure, can effectively adsorb heavy metal ions and is easy to separate from pollutants. Compared with single graphene aerogel, the GO / ZIF-8 / CMC composite aerogel increases the number and dispersion of adsorption sites by introducing carboxymethyl cellulose, improves the adsorption capacity and efficiency of pollutants, and at the same time, the introduction of cellulose can also enhance the stability and anti-pollution ability of the material and extend its service life.
[0082] GO / ZIF-8 / CMC composite aerogel introduces CMC, which can not only increase its adsorption performance, but also significantly improve the mechanical stability of the aerogel. Therefore, after adsorption saturation, it can be recycled through a simple regeneration operation (desorption in low-concentration hydrochloric acid, freeze-drying), reducing material consumption and environmental pollution. Compared with single rGO aerogel, GO / ZIF-8 / CMC composite aerogel can be regenerated due to the metal organic framework and cellulose, reducing costs and energy consumption. The composite aerogel has better sustainability and economy during long-term use.
[0083] The GO / ZIF-8 / CMC composite aerogel of the present invention has broad application prospects in the field of sewage treatment. It can not only be used for the adsorption and removal of heavy metal ions, but also can be combined with other technologies such as photocatalysis and biodegradation to further improve the sewage treatment effect. For example, it can be used to prepare film-forming materials or overall adsorption devices to improve the convenience and processing capacity of treatment. Its application fields cover industrial wastewater treatment, drinking water purification and other fields.
[0084] The above description is only a preferred embodiment of the present invention, and does not limit the scope of the present invention. Any equivalent transformations made using the contents of the present invention description and drawings, or directly or indirectly applied in other related technical fields, are also included in the protection scope of the present invention.
Claims
1. A method for preparing a GO / ZIF-8 / CMC composite aerogel, characterized in that: The specific steps are as follows: (1) dispersing graphene oxide in water to obtain a graphene oxide dispersion; (2) dissolving dimethyl imidazole zinc salt in ammonia water and dissolving carboxymethyl cellulose by heating with water, adding the two salts together to the graphene oxide dispersion prepared in step (1), and ultrasonically dispersing the mixture for 10 to 30 minutes to obtain a mixed solution; (3) adding a reducing agent to the mixed solution of step (2), mixing well and performing a hydrothermal self-assembly reaction to obtain a composite hydrogel, and freeze-drying to obtain a GO / ZIF-8 / CMC composite aerogel.
2. The method for preparing the GO / ZIF-8 / CMC composite aerogel according to claim 1, characterized in that: Step (2) Carboxymethyl cellulose is dissolved by heating water to above 40°C.
3. The method for preparing the GO / ZIF-8 / CMC composite aerogel according to claim 1, characterized in that: The specific preparation process of dimethylimidazole zinc salt in step (2) is as follows: Dissolve Zn(NO3)2·6H2O in deionized water, stir magnetically for 1 to 2 hours to disperse evenly to obtain a zinc nitrate solution, dissolve 2-methylimidazole in methanol, stir magnetically for 1 to 2 hours to disperse evenly to obtain a 2-methylimidazole solution, slowly pour the zinc nitrate solution into the 2-methylimidazole solution, stir magnetically for 12 to 16 hours, the mixed solution gradually becomes turbid, and as the stirring time increases, the solution becomes milky white, and then centrifuge, freeze-dry, and grind to obtain dimethylimidazole zinc salt powder.
4. The method for preparing the GO / ZIF-8 / CMC composite aerogel according to claim 3, characterized in that: The mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 4 to 8:
1.
5. The method for preparing the GO / ZIF-8 / CMC composite aerogel according to claim 1, characterized in that: The mass ratio of graphene oxide, dimethylimidazole zinc salt and carboxymethyl cellulose in the mixed solution of step (2) is 1-3:0.1-0.5:0.25-1.
6. The method for preparing the GO / ZIF-8 / CMC composite aerogel according to claim 1, characterized in that: In step (3), the reducing agent is thiourea, and the mass ratio of graphene oxide to thiourea is 1:3-4.
7. The method for preparing the GO / ZIF-8 / CMC composite aerogel according to claim 1, characterized in that: The temperature of the hydrothermal self-assembly reaction in step (3) is 90-100° C., and the reaction time is 5-7 hours.
8. The GO / ZIF-8 / CMC composite aerogel prepared by the preparation method of claim 1 is used as an adsorbent to adsorb heavy metal ions in sewage.
Citation Information
Patent Citations
Cellulose based three-dimensional multihole ZIF-8 / aerogel for adsorbing heavy metal ions and preparation method of cellulose based three-dimensional multihole ZIF-8 / aerogel
CN107376880A
Preparation method of graphene composite material with efficient adsorbability to sulfa antibiotics
CN108579674A
Surface functionalized graphene material, preparation method thereof, detection method and sensor
CN110386600A
Vulcanized graphene sponge composite material as well as preparation method and application thereof
CN110711565A
Thiosemicarbazide modified magnetic graphene oxide adsorbent and preparation method and application thereof
CN111229167A